Laparoscopic Reduction of Intussusception in Children: Role in Primary and revisional Reduction after Failed Non-Surgical Therapies - Almaramhy, Hamdi H. (International Journal of Health Sciences, 2011)
Background and objective: With the advent of laparoscopy into pediatric surgical filed and with experience gaining, as well as, improvement in instrumentation, it has been used in management of different conditions, including intussusception. However, there is no universal acceptance regarding its role in reduction of intussusception. This is due to the early reports of high conversion rate and the concern of missing a lead point. The aim of this article is to review the literatures about safety and efficacy of laparoscopy in intussusception management and the limitations as well as formulating a working algorithm for management of intussusceptions in pediatric age group up to 18 years. Up to my knowledge this is the first review article in this subject. Method: A comprehensive review of the English literature in Pub Med searching engine was conducted with key words laparoscopy, intussusception, management of intussusception, minimal invasive surgery and intussusception, laparoscopic reduction of intussusception, between 1996 and2009 .The results yielded were further explored for citation regarding the role of laparoscopy in reduction of intussusception. Results: The success rate increased from 57% in 1997 to 91% in 2009 while the conversion rate decreased from 43% in 1997 to 9% in 2009.The presence of a lead point and/or ischemic bowel were the main reasons for conversion in the initial reports. Conclusion: Laparoscopy is a safe and efficient method for reduction of intussusception.The presence of a lead point or necrotic bowel is no more indication for conversion to open surgery. Laparoscopy should be an integral tool in the management algorithm of intussusception. Keywords: intussusception reduction, laparoscopy in children, role of laparoscopy in intussusception.